The growth multiplier and a general theory of economic growth - Mishra, Vikas (Bombay : New York , Asia Pub. House, 1962)
This is descriptive analysis of dynamic input-output model. The book consists of 2 parts. Part I discusses the basic concepts and definitions and presents an analytic framework which he uses to discuss the way the process of economic growth could start and develop within the framework of this system. Part II examines economic evolution in the expansive time-horizon and shows the extent the analytical framework can be applied to explain the present and future of an economic society.
lje 19/10/18
Loans
Keywords: Economic growth; Economic development; Capital investments